PENERAPAN SISTEM IDENTIFIKASI BUNGA SEBAGAI MEDIA PROMOSI DI LINGKUNGAN LEREK, KELURAHAN GOMBENGSARI, KABUPATEN BANYUWANGI - Mulyadi, Adi; As’ari, Hasyim; Roisul Amin, Muhammad Zainal (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The potential of natural resources in Lerek Neighborhood, Gombengsari Village, Kalipuro District, Banyuwangi Regency has increased from 2020-2023. However, the potential experienced obstacles related to PSDA branding caused by Pokdarwis lack of knowledge with technological advances. Although branding has been carried out by the Government and Pokdarwis, community income is still low at 18.1%. So, one of the efforts needed by partners to increase income by branding Kampung Bunga destinations using the implementation of identification system technology. The implementation of the identification system is used to facilitate the Flower Group in classifying various types of flowers in Gombengsari Village, Banyuwangi Regency. The purpose of this activity is as a medium for promoting local and national Flower Village tourism. The identification system uses the Convolutional Neural Network method for the classification of six types of flowers in Kiosk Intan. The identification results show that six types of flowers have different levels of accuracy (rose 100%, orchid 90%, jasmine 85%, frangipani 90%, chrysanthemum 90% and sedap malam 90%) with a traning time of 0.169 seconds and a test of 0.171 seconds. While the evaluation results from the Flower Group user partners related to the application of the identification system help in the classification of flower types with an accuracy level of ± 85-90%.